Luaran Terapi Berdasarkan Jenis Pemberian Analgetik pada Pasien Pasca Operasi Ortopedi - Nurul Irna Windari; Zullies Ikawati, Apt.; Eni Purwaningtyastuti (Faculty of Pharmacy, Universitas Gadjah Mada)
Postoperative pain was suffered by 80% of the total patients. One of the many surgical procedures performed is orthopedics. Ketorolac and fentanyl are often used for postoperative orthopedic pain. Appropriate postoperative pain management with adequate analgesic administration will accelerate pain reduction and shorten the patient's hospital stay. This study aims to determine the difference in the effect of continuous fentanyl and intravenous ketorolac on pain targets achievement and Length of Stay (LOS) of patients after orthopedic surgery. This study is a prospective cohort study, involving inpatients after orthopedic surgery in Dr. Sardjito Yogyakarta in July-October 2019. The independent variable is continuous fentanyl and intravenous ketorolac, while the dependent variable is the achievement of pain targets and LOS. The analysis was conducted by Fisher's exact test, Mann Whitney's test, and multivariate analysis to determine the dominance of variables on the research outcomes. There were 59 patients after orthopedic surgery in this study. A total of 34 patients in the continuous fentanyil group and 25 patients in the intravenous ketorolac group. There was no difference in the effect of continuous fentanyl administration and intravenous ketorolac on pain targets achievement (P = 0.711), while there were differences in the effect of continuous fentanyl administration and intravenous ketorolac on the average LOS of patients in the hospital (P = 0,000). Continuous fentanyl and intravenous ketorolac can both produce the achievement of adequate postoperative orthopedic pain targets, but the mean LOS becomes shorter in patients with intravenous ketorolac.